PEMBINAAN KAUM PEREMPUAN GMIT SION OEPURA KUPANG SEBAGAI UPAYA MENCEGAH DAN MENGURANGI KEKERASAN PEREMPUAN - Ndeo, Jeanne; Tahalele, Novi Kristiani; Tagu Sunga, Seli Antonia; Taneo, Imelda Sara (Jurnal PKM Setiadharma, 2024)
Violence against women is inevitable in today’s society. This violence cannot be rejected because the apparent fact is that women cannot resist or reduce it. One of the factors causing it is the stigma about women who should be in second place in society so that they must obey and not argue, which is still rooted very firmly. On this basis, the activities of Dedication to the Society through seminars are carried out. This activity aims to shape and change the paradigm of thinking about the identity and existence of women in stigmatization so that they are capable and influential in the struggle to end violence. The methods used in this activity are lectures, discussions, opinions, and presentations. As for the outcome of this activity, the women at GMIT Jemaat Sion Oepura Kupang have a new paradigm of thinking about women, specifically their identity and their position in a patriarchal society, to reduce and break the chain of violence against women.